Evaluation of Citrus × Microcitrus Hybrid Scions - Albrecht, Ute (EDIS, 2022)
This article describes a new project designed to develop and test novel hybrids to be used as scions and which combine the HLB tolerance traits of Australian limes (Microcitrus) and the fruit characteristics of Citrus. Field trials that are in progress in Florida are described; comparable field trials are being conducted in California and Texas.